(untitled) (LEGAL DIALOGICA, 2025)
A.Jessica Ayu Ma’rifa. 04020210310: “Investigation of Illegal Cosmetics Distribution Crimes in Makassar (Study on the South Sulawesi Regional Police)”. Under the guidance of Mrs. Hj. Nur Fadhilah Mappaselleng. As the chief supervisor and Mr. Muh Zulkifli Muhdar..as the member supervisor. This study aims to find out and explain the process of investigating illegal cosmetics distribution crimes in Makassar and to find out and explain the factors that influence the investigation of illegal cosmetics distribution crimes in Makassar. This study uses an empirical legal method with a qualitative descriptive approach. Data were obtained through interviews and data collection with law enforcement officers. The results of this study indicate that the process of investigating illegal cosmetics distribution crimes in Makassar by the South Sulawesi Regional Police is basically carried out in accordance with the provisions of the applicable Criminal Procedure Code (KUHAP). The factors that hinder the process of investigating illegal cosmetics distribution crimes in Makassar. This research recommendation requires and is important to have a more efficient coordination system between police investigators and BPOM officers to facilitate the investigation process until the determination of suspects. Abstrak: A.Jessica Ayu Ma’rifa. 04020210310: “Penyidikan Tindak Pidana Peredaran Kosmetik Ilegal Di Makassar (Studi Pada Kepolisan daerah Sulawesi Selatan)”. Dibawah bimbingan ibu Hj. Nur Fadhilah Mappaselleng. Selaku pembimbing ketua dan bapak Muh Zulkifli Muhdar..selaku Pembimbing anggota. Penelitian ini bertujuan Untuk Mengetahui dan menjalaskan proses penyidikan tindak pidana peredaran kosmetik ilegal di Makassar serta Mengetahui dan menjelaskan faktor-faktor yang mempengaruhi penyidikan tindak pidana peredaran kosmetik ilegal di Makassar. Penelitian ini menggunakan metode yuridis empiris dengan pendekatan deskriptif kualitatif. Data diperoleh melalui, wawancara dan pengumpulan data dengan aparat penegak hukum. Hasil penelitian ini menunjukkan bahwa proses penyidikan tindak pidana peredaran kosmetik ilegal dimakassar oleh kepolisian daerah Sulawesi selatan pada dasarnya dilaksanakan sesuai dengan ketentuan Kitab Undang-Undang Hukum Acara Pidan (KUHAP) yang berlaku. Adapun faktor-faktor yang menghambat proses penyidikan tindak pidana peredaran kosmetik ilegal dimakassar. Rekomendasi penelitian ini perlu dan penting adanya sistem koordinasi yang lebih efisien antara penyidik kepolisian dengan Petugas BPOM guna mempermudah proses penyidikan hingga penetapan tersangka.